The effect of anti-helicobacter pylori with iron folate supplementation and only iron folate supplementation of helicobacter pylori infected CagA positive Indian non-pregnant women - Sen, Bandana (International Journal Of Community Medicine And Public Health, 2025)
Background: Helicobacter pylori is a type of bacteria that infects our stomach and small intestine. This study aimed to evaluate response to H. pylori infection of the anti H. pylori therapy with iron folate supplementation and only iron folate supplementation of CagA positive and CagA negative women. Methods: The non-pregnant Indian women (18-35 years) whose Hemoglobin<115 gm/dl, body mass index<20 kg/m2 and H. pylori positive status were recruited in our study. H. pylori positive strains women were divided two groups CagA positive and CagA negative. Depending on types of supplementations, both CagA positive and CagA negative women were divided by two groups treatment and Control. Treatment group received 7 days anti H. pylori therapy then 3 months iron folate supplementation. Control group received only iron folate supplementation for 3 months. Results: Total 81 women were H. pylori infected and among them 65 (80.2%) were CagA positive and 16 (19.8%) were CagA negative. There were no significant correlations of hematological parameters between H. pylori infected CagA positive and CagA negative women. At baseline Hb, MCV, MCH and TIBC value was comparatively lower of CagA positive than CagA negative women. After 3 months intervention Hb, MCV and Ferritin were increased significantly (p<0.05) higher in treatment group than control group of CagA positive women. Conclusions: After 3 months supplementation of anti H. pylori therapy with iron folate supplementation of CagA positive strains was better response than CagA negative strains of child bearing aged non pregnant women.